2021
DOI: 10.1038/s41467-021-23836-z
|View full text |Cite
|
Sign up to set email alerts
|

Sugar phosphate activation of the stress sensor eIF2B

Abstract: The multi-subunit translation initiation factor eIF2B is a control node for protein synthesis. eIF2B activity is canonically modulated through stress-responsive phosphorylation of its substrate eIF2. The eIF2B regulatory subcomplex is evolutionarily related to sugar-metabolizing enzymes, but the biological relevance of this relationship was unknown. To identify natural ligands that might regulate eIF2B, we conduct unbiased binding- and activity-based screens followed by structural studies. We find that sugar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…It was recently demonstrated that eIF2Bα can bind sugar phosphates to a different regulatory pocket, which also enhanced eIF2B activity ( Hao et al., 2021 ; Kuhle et al., 2015 ). Hence eIF2B has at least 2 pockets to which cell metabolites can bind and influence its activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that eIF2Bα can bind sugar phosphates to a different regulatory pocket, which also enhanced eIF2B activity ( Hao et al., 2021 ; Kuhle et al., 2015 ). Hence eIF2B has at least 2 pockets to which cell metabolites can bind and influence its activity.…”
Section: Resultsmentioning
confidence: 99%
“…eIF2Bαβδ subunits show structural similarity to ribose bisphosphate isomerases, and Kuhle and colleagues established that both AMP and GMP can bind to eIF2Bα ( Kuhle et al., 2015 ). The role of ligand binding to eIF2Bα was very recently expanded to show that sugar phosphates including fructose-6-phosphate can bind eIF2Bα to enhance its GEF activity, demonstrating that eIF2B activity can be modified by naturally occurring ligands other than phosphorylated eIF2 ( Hao et al., 2021 ). It was previously shown that GTP can directly bind to purified yeast eIF2B, with an apparent K d of 1 μM ( Nika et al., 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of known moonlighting proteins has increased drastically in recent years ( Jeffery, 2020 ; Liu and Jeffery, 2020 ; Singh and Bhalla, 2020 ; Beaufay et al, 2021 ; Rodríguez-Saavedra et al, 2021 ; Turek and Irving, 2021 ). An indication that the archaeal proteins might have two different functions is the recent observation that the eukaryotic eIF2Bα still has the ability to bind sugar phosphates with high affinity, e.g., fructose-6-phosphate has a K D of 9.4μM ( Hao et al, 2021 ). The binding of sugar phosphate enhances the formation of the complete eIF2B decamer.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that eIF2Ba can bind sugar phosphates to a different regulatory pocket, which also enhanced eIF2B activity (Hao et al, 2021;Kuhle et al, 2015). Hence eIF2B has at least 2 pockets to which cell metabolites can bind and influence its activity.…”
Section: Eif2b(gk66r)-eif2 Interaction Is Gtp Sensitivementioning
confidence: 99%
“…eIF2Babd subunits show structural similarity to ribose bisphosphate isomerases, and Kuhle and colleagues established that both AMP and GMP can bind to eIF2Ba (Kuhle et al, 2015). The role of ligand binding to eIF2Ba was very recently expanded to show that sugar phosphates including fructose-6-phosphate can bind eIF2Ba to enhance its GEF activity, demonstrating that eIF2B activity can be modified by naturally occurring ligands other than phosphorylated eIF2 (Hao et al, 2021). It was previously shown that GTP can directly bind to purified yeast eIF2B, with an apparent K d of 1 mM (Nika et al, 2000).…”
Section: Introductionmentioning
confidence: 99%